Digital Storytelling across Disciplinary Horizons: A Bibliometric Exploration through Physics, Mathematics, Chemistry, and Social Sciences - Davis, Desmin; Praveen G, Manoj; K, Ashna (Journal of educational technology development and exchange, 2025)
This study aims to know the key publication trends and patterns in digital storytelling research and to find the most influential papers, authors, journals, funding sponsors, sources, and countries that contributed to digital storytelling research from 2013 to 2023. This was examined through a systematic bibliometric analysis conducted on 508 documents collected from the Scopus database based on particular inclusion and exclusion criteria. Bibliometric patterns were obtained using the VOS viewer software. The findings indicated that the digital storytelling research field is emerging and shows growing interest in this particular field. The increasing citation trend shows its importance across various disciplines and applications. The most influential paper on digital storytelling was by Willox et al. (2013) which narrated the methodological process they developed to engage a remote community in northern Labrador on climate change. Chan, C. was the most influential author who wrote about the role of digital storytelling in social work, technology, critical thinking disposition in youth civic engagement, higher education, etc. This study suggests that if we are ready to implement digital storytelling in problem-solving, it will impact students’ conceptual understanding and learning will become more fruitful and life-oriented.